Earth-abundant Ni-Zn nanocrystals for efficient alkyne semihydrogenation catalysis - Jasper Clarysse; Jordan De Jesus Silva; Yunhua Xing; Seraphine B. X. Y. Zhang; Scott R. Docherty; Nuri Yazdani; Maksym Yarema; Christophe Copéret; Vanessa Wood (Nature Communications)
Abstract The development of catalysts that are based on earth-abundant metals remains a grand challenge. Alloy nanocrystals (NCs) form an emerging class of heterogeneous catalysts, offering the promise of small, uniform catalysts with composition-control. Here, we report the synthesis of small Ni and bimetallic Ni-X (X= Zn, Ga, In) NCs for alkyne semihydrogenation catalysis. We show that Ni3Zn NCs are particularly reactive and selective under mild reaction conditions and at low loadings. While bimetallic NCs are all more selective than pure Ni NCs, Ni-Zn NCs also maintain excellent reactivity compared to Ni-Ga and Ni-In alloys. Ab-initio calculations can explain the differences in reactivity, indicating that, unlike Ga and In, Zn atoms interact with the substrates. We further show that Ni3Zn NCs are robust and tolerate a broad range of substrates, which may be linked to the favorable amine-terminated surface.